CORROSION RESISTANCE OF POLYMER-SILICA-CALCITE TEXTURED SURFACES - ЮН, Ц.; БАКЛАН, Д. В.; МИРОНЮК, О. В. (Technologies and Engineering, 2024)
Purpose. Determine the relationship between the corrosion resistance properties of the additive coatings and the fractional composition of the components that form the texture. Methodology. In this work, an additive bifractional texture was created on the basis of a styrene-butyl acrylate copolymer as a binder and hydrophobized silica nanoparticles and hydrophobized calcium carbonate microparticles as texture-forming fillers. The coatings were applied to the substrate by pneumatic means. To assess the corrosion resistance, the samples were immersed in distilled water and salt solution. To assess the change in properties, the angle of wetting with water (the sitting drop method) was used, and scanning electron microscopy was used to observe structural changes on the surface. Electrochemical impedance spectroscopy and potentiodynamic polarization curves were used to evaluate the corrosion potential. Findings. The results show that the obtained coatings are not completely resistant to prolonged exposure to water. The main defects are cracking and an increase in surface polarity. This leads to a drop in the angle of wetting with water. An additional deterioration in the water-repellent properties is due to a decrease in the adhesion of the polymer to the filler. According to the studies of self-corrosion potential, the sample with the largest amount of micro-sized filler and the lowest polymer content was the most stable. For this sample, no loss of hydrophobic properties was observed after prolonged immersion in a corrosive environment, although cracks formed on the surface. Originality. For the first time, significant changes in corrosion resistance have been shown to be possible for additive coatings obtained by pneumatic spraying with a hierarchical surface structure, depending on the fractional ratio of micro- and nanosized particles that form the texture. Practical value. The composition of an additive coating based on a styrene-acrylic polymer and structure-forming particles has been developed, which is characterized by increased corrosion resistance due to the fractional ratio, which allows forming a structure with high water repellency.